Downregulation of Dopamine D1-like Receptor Pathways of GABAergic Interneurons in the Anterior Cingulate Cortex of Spontaneously Hypertensive Rats. (1st December 2018) - Satoh, Hiromasa; Suzuki, Hidenori; Saitow, Fumihito
Highlights: Dopamine enhances GABAergic transmission onto layer V pyramidal cells in the anterior cingulate cortex. The modulatory action is involved with activation of D1-like receptor at GABAergic interneurons. GABAergic synapses in the anterior cingulate cortex of ADHD model rat exhibit diminution of the modulatory action. Hypofunction of the dopamine modulatory action of GABAergic transmission may contribute to the pathophysiology in ADHD. Abstract: Deficits in dopaminergic function are thought to underlie attention-deficit/hyperactivity disorder (ADHD). Dopaminergic neurons are the main source of dopamine (DA), a neurotransmitter that acts as a neuromodulator of cognitive function in the prefrontal cortex, including the anterior cingulate cortex (ACC), which receives dopaminergic inputs from the ventral tegmental area. The spontaneously hypertensive rat (SHR) has been widely studied as an animal model of ADHD. The aim of the current study was to investigate the pathophysiological mechanisms of ADHD by examining DA modulation of γ-aminobutyric acid neural (GABAergic) transmission recorded from layer V pyramidal cells of the ACC in SHR compared to control Wistar–Kyoto rats (WKY). Our results showed that DA activity increased the frequency of both miniature and spontaneous inhibitory postsynaptic currents (IPSCs) in control WKY, but not in SHRs. Furthermore, DA activity enhanced the amplitude of evoked and unitary IPSCs from fast-spiking interneurons; the amplitude was also larger in control WKY than in SHRs. Notably, the amplitude of evoked IPSCs was enhanced by the activation of D1-like receptor-mediated pathways. These results suggest that hypofunction of D1-like receptor-mediated regulation of GABAergic inhibitory synaptic transmission onto layer V pyramidal cells of the ACC may contribute to the pathophysiology of ADHD.